Safranin-O removal from aqueous solutions using lignin nanoparticle-g-polyacrylic acid adsorbent: Synthesis, properties, and application - J Azimvand; Kh Didehban; SA Mirshokraie (Adsorption Science & Technology)
In this study, alkali lignin modified by ethylene glycol and lignin nanoparticles was prepared through acid precipitation technology. Lignin nanoparticle-g-polyacrylic acid adsorbent was prepared using copolymerization reactions between lignin nanoparticle and polyacrylic acid in the presence of potassium persulfate as the radical initiator. Then, lignin nanoparticle-g-polyacrylic acid adsorbent was used to remove Safranin-O from an aqueous environment. The adsorbent structures and morphologies of lignin nanoparticle and lignin nanoparticle-g-polyacrylic acid adsorbent were investigated using scanning electron microscopy, Fourier transform infrared spectroscopy, and thermogravimetric analysis. Nanoparticle sizes were assessed using dynamic light scattering. Equilibrium isotherms were compared using the Langmuir, Freundlich, and Temkin adsorption models. Both adsorbent lignin nanoparticle and lignin nanoparticle-g-polyacrylic acid adsorbent showed good agreement with the Langmuir isotherm. The maximum adsorption capacities of lignin nanoparticle and lignin nanoparticle-g-polyacrylic acid adsorbent reached 99 and 138.88 mg g −1 using model-like, pseudo-second-order, and intraparticle diffusion, respectively. Experimental results showed that adsorbent lignin nanoparticle and lignin nanoparticle-g-polyacrylic acid adsorbent followed the pseudo-second order kinetic model.